The emergence of pastoral authority in the French Reformed Church, c.1555-c.1572 - Braghi, Gianmarco. (Leiden ; Boston)
xi, 324 sayfa
Keywords: “In The Emergence of Pastoral Authority in the French Reformed Church, c.1555-c.1572, Gianmarco Braghi offers a broad overview of the issues and ambiguities connected to the implementation of the authority of the first generation of Geneva-trained French Reformed pastors and of their implications for the character and identity of the early French Reformed movement at large, using them as a prism for historical analysis of the transition to loose evangelicalism to a nascent synodal-consistorial network of Reformed congregations scattered across the kingdom of France.“ --